Occurrence of Trihalomethanes in Chlorinated Waters from Different Sources Used for Urban Supply - Melo, Armindo (2017)
Trihalomethanes (THMs) are the most common disinfection by-products formed by the reaction of chlorine and/or bromide with organic matter. Total THMs in chlorinated treated water are defined as the sum of the concentrations of chloroform (TCM), bromodichloromethane (BDCM), dibromochloromethane (DBCM), and bromoform (TBM). The monitoring of trihalomethanes in distribution tap water collected in from five regions of Portugal, from North to South, in a total of 33 samples, during spring to summer season, is described. Solid phase microextraction coupled to gas chromatography and electron capture detector methodology was applied to determine whether THMs concentrations in urban water supply systems are is in agreement with European Regulations. It was found a great discrepancy in total THMs concentration values, with concentrations varying from 1.8-97.7 μg/L, although the results were below the European parametric value of 100 μg/L. Regarding the Environmental Protection Agency regulations, however, only 97% of samples fulfilled the established criterion of 80 μg/L. and investigate if the individual compounds trihalomethanes content in was also investigated in order to determine if there is observed distribution tap water follows a common or a different THMs pattern in close geographical areas. In the geographical areas under study, mean values of concentrations measured revealed two different clusters: one including the three groups from the North geographical areas, with samples revealing a similar pattern (TCM>BDCM>DBCM>TBM), and another including the two groups from South with a different THMs pattern (DBCM>BDCM>TCM>TBM). A great degree of variation in the concentrations of THMs in tap water was observed, although the results the total THMs concentrations were below the European parametric value (100 μg/L). Mean results of samples grouped by five geographical areas revealed a similar pattern in samples collected from North and Centre TCM>BDCM>DBCM>TBM, whereas samples from South presented a different pattern, DBCM>BDCM>TCM>TBM. The origin of raw water (surface or groundwater) seems to influence this different pattern formation of brominated compounds.